2022
DOI: 10.1371/journal.pone.0270369
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider perspectives on delivering next generation rotavirus vaccines in five low-to-middle-income countries

Abstract: Background Live oral rotavirus vaccines (LORVs) have significantly reduced rotavirus hospitalizations and deaths worldwide. However, LORVs are less effective in low- and middle-income countries (LMICs). Next-generation rotavirus vaccines (NGRVs) may be more effective but require administration by injection or a neonatal oral dose, adding operational complexity. Healthcare providers (HPs) were interviewed to assess rotavirus vaccine preferences and identify delivery issues as part of an NGRV value proposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…These results, presented in more detail by Mooney et al [31], suggest that introduction of any NGRV would face specific challenges in some settings and highlight the need for more education, training, and tailored messages for healthcare providers.…”
Section: High-level Findings From Healthcare Provider Interviewsmentioning
confidence: 88%
See 2 more Smart Citations
“…These results, presented in more detail by Mooney et al [31], suggest that introduction of any NGRV would face specific challenges in some settings and highlight the need for more education, training, and tailored messages for healthcare providers.…”
Section: High-level Findings From Healthcare Provider Interviewsmentioning
confidence: 88%
“…Whether delivered alone or co-administered with LORV, iNGRV-DTP emerged as the most cost-effective option compared both to existing products and oNGRVs [28]. It was also the option most preferred by country stakeholders against all other options [31], and, by extension, to likely have the greatest market demand, whether its efficacy was similar or superior to that of existing products. The combined findings from all three major analysesthe health impact and economic analysis, the feasibility and acceptability study, and the demand forecast-underscore a need for funders and manufacturers to consider prioritizing the necessary iNGRV compatibility and combinability studies with DTP-pentavalent and DTP-hexavalent, even if iNGRV efficacy ends up being no greater than that of existing LORVs [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond Shigella , historical efforts to gain insight into preferences around vaccine attributes have seldom involved systematic surveys of those most directly involved at the country level. Recent precedents by Price and Mooney et al considered novel rotavirus vaccines which found similar preferences for oral and combination presentations [43] , [44] . Our study is timely, since Shigella vaccine candidates are still in development, providing manufacturers an opportunity to incorporate our findings into clinical trials plans, such as evaluating vaccine impact beyond diarrhea by integrating a stunting endpoint into Phase 3 clinical studies.…”
Section: Discussionmentioning
confidence: 99%